HEPATOPROTECTIVE ACTIVITY OF VARIOUS EXTRACTS OF CLAUSENA DENTATA (WILLD.) ROEM. (SYN. CLAUSENA WILLDENOVII WIGHT. AND ARN.) RUTACEAE - Kamaraj, Raju; Maduram, Annamalai; N, Raman (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: Clausena (Rutaceae) is a genus of about 23 species of unarmed trees and shrubs. The stem bark of Clausena dentata is used in veterinary medicine for the treatment of wounds and sprains. Even though C. dentata has a lot of potential medical uses, the study on pharmacological activities is in scarce. The present study was undertaken hepatoprotective activity of various extracts of C. dentata. Methods: The plant C. dentata was collected from Kadagaman, near Tiruvannamalai, Tamil Nadu, India. The dry powder of stem bark (2.5 kg) was first soaked in hexane for 24 hrs. The extract was suction filtered. This was repeated for two more days, and similar extracts were pooled together and concentrated at 40°C using Buchi R - 153 Rotavapor. The residual plant material was extracted successively with chloroform and methanol same manner. Preliminary phytochemical test and hepatoprotective activity of various extracts of C. dentata against carbon tetrachloride (CCl4) induced hepatotoxicity in rats were carried out. Biochemical and histopathological changes were observed. Results: The highly significant (p<0.01) reduction in the levels of serums glutamic oxaloacetic transaminase, glutamic pyruvic transaminase, alkaline phosphatase, and bilirubin observed in the study in rats simultaneously treated with C. dentata extracts and CCl4 as compared to CCl4 alone treated. Conclusion: CCl4 induced hepatic damage was counteracted by the extracts of C. dentata. Changes were observed in enzymatic and histopathological level, when compared to CCl4 alone treated group.